Identification of Group 2 Innate Lymphoid Cells in Mouse Lung, Liver, Small Intestine, Bone Marrow, and Mediastinal and Mesenteric Lymph Nodes. (17th April 2019) - Romera‐Hernández, Mónica; Mathä, Laura; Steer, Catherine A.; Ghaedi, Maryam; Takei, Fumio
Abstract: Innate lymphoid cells (ILCs) are a heterogeneous family of lymphocytes that populate barrier and non‐barrier tissues. ILCs regulate immune responses to pathogens and commensals but also sustain metabolic homeostasis, tissue remodeling after injury and establish dialogue with the nervous system. ILCs rapidly become activated in the absence of adaptive antigen receptors by responding to signaling molecules provided by hematopoietic or non‐hematopoietic cells. Here we provide protocols designed for processing the lung, liver, small intestine, bone marrow, mediastinal and mesenteric lymph nodes in order to obtain a purified leukocyte fraction of cells, in which ILC2 enrichment is optimized. In addition, we describe in detail the methodologies used to activate ILC2s and the assays necessary for the detection of their effector cytokines. We highlight the differences in ILC2 characterization within distinct tissues that we have recently identified. © 2019 by John Wiley & Sons, Inc.